Analysis of Liquefaction Potential Based on Standard Penetration Test (SPT) Data (Case Study: Transit Oriented Development Project in East Jakarta) - Enden Mina; Rama Indera Kusuma; Woelandari Fathonah; Ina Asha Nurjanah; Prastika Wahid Santoso; Bayu Darmawan (Jurnal Fondasi, 2026)
Liquefaction is a phenomenon in which solid soil becomes liquid, affecting soil stability due to an increase in pore water pressure. Liquefaction can cause damage to building structures and infrastructure, potentially resulting in significant losses. An analysis of liquefaction potential is required and is conducted using field Standard Penetration Test data. The method used is based on the approach developed by Seed and Idriss using SPT data. This study aims to determine the Safety Factor (FS) against liquefaction by comparing the Cyclic Stress Ratio (CSR) and the Cyclic Resistance Ratio (CRR). Soil layers are categorized as having liquefaction potential if the obtained FS value is less than one. The results show that the soil profile at the study location consists of medium to stiff clay and medium to dense sand, as indicated by relatively high average N-SPT values. The SPT calculations produce high CRR values, and the CSR values at the study location are also relatively high. This is caused by the earthquake acceleration value obtained from the DEEPSOIL software, which is 0.4 g. The safety factor values at the study location range from 0.4 to 0.8 at all SPT points, where FS values less than 1 indicate that the soil has the potential to undergo liquefaction.